Let's prevent repeat of use of WMD as in Hiroshima and Nagasaki - Abd Razak, Dzulkifli (2003)
THE inaugural World Peace Forum opened yesterday in Kuala Lumpur, a date that coincided with a tragic event of untold proportions, though not as well known as the devastation of the Japanese in Hiroshima. August 6 was the day that the bombing of Hiroshima took place at precisely 8.15am in 1945. It is regarded as a single largest mass irradiation in history, perhaps the first use of a weapon of mass destruction. While Hiroshima is so much talked about, another tragic incident of equal dimension just three days later is being overshadowed. It took place on Aug 9, also in Japan, but involving a different city, Nagasaki.